Political socialization and prospects for reconciliation among youth in Vukovar, Croatia - Reidy, Catherine Margaret (2013)
Political socialization, defined as “those developmental processes through which individuals acquire political orientations and patterns of behavior” (Allen, 1989, p.57), is important for the development of youth’s attitudes toward reconciliation in Vukovar, Croatia. Ethnic tension and violence replaced inter-group harmony in Vukovar as a result of the 1991-1995 wars during the dissolution of the former Yugoslavia. Many youth were born after the height of the violence of the 1990s, offering potential for the reduction of inter-group conflict and a movement toward positive inter-group relations. Yet, youth are also exposed to the political attitudes of others who survived the war. If processes of political socialization work to maintain the status quo, youth may perpetuate conflict ; on the other hand, youth may also be encouraged to overcome historic divides. The development of peace in Vukovar is contingent on youth’s prospects for reconciliation. The current paper explores the processes of the political socialization of youth in Vukovar, Croatia, as these processes influence youth’s conceptions of future inter-group relations and reconciliation among Croats and Serbs. The analyses include qualitative data from ten focus group interviews conducted among 11-, 13-, and 15-year-olds, mothers, and fathers (N=66) from Serb (53%) and Croat (47%) ethnic groups. The Constant Comparative Method (Maykut & Morehouse, 1994) was used to analyze qualitative transcripts. Results demonstrate a strong association between political socialization and youth’s prospects for reconciliation. Analyses indicate that parents, peers, schools, and media serve as key agents in the political socialization of youth. They influence youth’s attitudes toward the future through ethnic insults, approval and disapproval of friendships and relationships, storytelling about past conflict, and media broadcasts. Despite negative or polarizing messages and interactions, youth seek change. They demonstrate positive prospects for the future, indicating that reconciliation among Croats and Serbs is possible, particularly if youth are the generation to initiate it. These findings have implications for interventions that aim to foster the development of positive inter-group relations, and may generalize to other settings of inter-group tension.